A Study on Linguistic Features of Advertisement: Exploring Linguistic and Cultural Aspects in Advertising (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The reports have addressed both linguistic andextra–linguistic features and trends in advertising and emphasized language andculture–specific elements. This paper also gives ideas for future studies,since nowadays, due to international marketing and increasing globalizationthere are more cultural transfers to be explored, as cultures are coming incontact far more frequently.